Bioethanol Production from Sugarcane Bagasse Using Neurospora intermedia in an Airlift Bioreactor - Elvi Restiawaty; Kindi Pyta Gani; Arinta Dewi; Linea Alfa Arina; Katarina Ika Kurniawati; Yogi Wibisono Budhi; Akhmaloka Akhmaloka (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Bagasse as solid waste in sugarcane industry can be utilized as one of the potential raw materials in the bioprocess industry. This research aims to investigate the conversion of bagasse to bioethanol using simultaneous saccharification and fermentation in an airlift bioreactor. Neurospora intermedia was used as a biological agent that carried out the saccharification and fermentation of sugarcane bagasse simultaneously for bioethanol production. Cell morphology of N. intermedia in the form of pellet was required to provide free movement in the axial flow of airlift bioreactor. The medium pH strongly affects the morphological shape of N. intermedia. Therefore, the formation of good pellets of inoculum was observed under acidic conditions, i.e. pH 3.0 – 3.5. The effect of the initial concentration of nutrient on the inoculum growth was also investigated. Inoculums cultured in potato dextrose broth (PDB) medium with a half the strength of the common nutrient concentration of PDB qualitatively indicated good growth in terms of the size and density of cells. The inoculums with good morphological form were fed into the airlift bioreactor, which already contained a liquid medium with initial pH of 3.5 and also contained pre-treated bagasse. In experiments using the airlift bioreactor, the pre-treated bagasse was added to various nutrient concentrations of the PDB infusion medium. The highest bioethanol production from bagasse was monitored in the medium culture of half strength PDB infusion. The yield of bioethanol obtained from total sugarcane bagasse and PDB in an air lift bioreactor achieved approximately 40%, which has an infusion medium with a half-strength PDB and initial pH of 3.0.